Austroasiatic loanwords in Austronesian languages - Mahdi, Waruno (UI Scholars Hub, 2024)
This paper investigates lexical borrowing from Austroasiatic into Austronesian languages. It does so for the following contact stages and interactions between these languages following the Austronesian overseas dispersal: (Stage 1) early contacts between Austroasiatic and Malayo-Polynesian particularly in the early Neolithic in the area encompassing mainland Southeast Asia, Northwest Kalimantan, and Sumatra, often resulting in the transmission of faunal terms; (Stage 2) interactions between speakers of Mon-Khmer and Malayo-Chamic languages during the early development of statehood; (Stage 3) exchange of terms in the period of early Khmer, Cham, and Malay kingdoms. Some of these transmissions can be shown to have taken place against the backdrop of the paramountcy of the kingdom of Funan. The latter stage also involves Sanskrit loanwords which were transmitted to Malayo-Polynesian via a Mon-Khmer language. The loanwords in this article are informative of Southeast Asia’s language history as well as the region’s cultural history.